2013
DOI: 10.1038/nmat3729
|View full text |Cite
|
Sign up to set email alerts
|

Onsager’s Wien effect on a lattice

Abstract: The second Wien effect describes the nonlinear, non-equilibrium response of a weak electrolyte in moderate to high electric fields. Onsager's 1934 electrodiffusion theory, along with various extensions, has been invoked for systems and phenomena as diverse as solar cells, surfactant solutions, water splitting reactions, dielectric liquids, electrohydrodynamic flow, water and ice physics, electrical double layers, non-ohmic conduction in semiconductors and oxide glasses, biochemical nerve response and magnetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 32 publications
5
60
0
1
Order By: Relevance
“…The latter is consistent with a recent specific-heat study that has suggested the onset of ordering correlations in this temperature range 26 , and also with neutron scattering evidence that reveals a gradual departure from pure spin-ice correlations (although no tendency to order) as Dy 2 Ti 2 O 7 is cooled to 0.3 K (refs 27,28). On the other hand, the 'dual electrolyte' of the monopole model shows a striking change of dynamics exactly in this temperature range, which is associated with the Wien effect for magnetic monopoles [29][30][31] . Future work will be aimed at distinguishing these possibilities, more closely connecting our results with intrinsic farfrom-equilibrium dynamics of a 16-vertex model 15 and applying the avalanche quench technique to other magnetic systems.…”
supporting
confidence: 57%
“…The latter is consistent with a recent specific-heat study that has suggested the onset of ordering correlations in this temperature range 26 , and also with neutron scattering evidence that reveals a gradual departure from pure spin-ice correlations (although no tendency to order) as Dy 2 Ti 2 O 7 is cooled to 0.3 K (refs 27,28). On the other hand, the 'dual electrolyte' of the monopole model shows a striking change of dynamics exactly in this temperature range, which is associated with the Wien effect for magnetic monopoles [29][30][31] . Future work will be aimed at distinguishing these possibilities, more closely connecting our results with intrinsic farfrom-equilibrium dynamics of a 16-vertex model 15 and applying the avalanche quench technique to other magnetic systems.…”
supporting
confidence: 57%
“…A strong applied field 'blows away' the screening cloud, and the correction disappears. An exponential decrease of κ/ √ F from its zero-field value, κ 0 /γ 0 , to its limiting high-field value, κ 0 , has been confirmed numerically 17 . The decay rate is determined only by γ 0 (see Methods).…”
mentioning
confidence: 61%
“…Various contributions to nonlinear dielectric effects have been identified: dielectric saturation [1][2][3][4], chemical changes [5,6], fieldinduced changes in barrier height [7,8], field-dependent charge densities [9,10], and elevations of configurational and real temperatures [11][12][13][14], analogous to microwave heating [15]. More recently, a theory that connects nonlinear dielectric behavior to the number of dynamically correlated particles or nontrivial length scales has gained considerable attention [16][17][18].…”
Section: Introductionmentioning
confidence: 99%